THE ROLE OF SITUATIONAL-ROLE GAMES IN THE FORMATION OF COMMUNICATIVE COMPETENCE OF STUDENTS - Khashimova , Shoira; Ziyovuddinova , Mukhlisa (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The article examines the role of situational role-playing games in developing students’ communicative competence in higher education. The relevance of interactive teaching methods within the competence-based approach is substantiated. The results of a pedagogical experiment aimed at identifying the effectiveness of role-playing games in the educational process are presented. It is concluded that the systematic use of situational role-playing games enhances students’ speaking skills, interpersonal communication abilities, argumentation, and critical thinking.